Effects of Cultural Dimensions on Teacher Identity: A Systematic Review - Yang Xiao Ci; Janaka Low, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
Teacher identity is a multifaceted construct influenced by various factors, including cultural dimensions. This systematic review aims to explore the effects of cultural dimensions on teacher identity. By synthesizing existing literature, we seek to provide insights into the ways in which cultural factors impact teachers' self-concept, teaching practices, and professional development. The review will also shed light on the implications for teacher education and the promotion of culturally responsive teaching. Through a comprehensive analysis of empirical studies, this research seeks to contribute to a deeper understanding of how culture shapes teacher identity in diverse educational contexts.